Strength-constrained unit commitment in IBR dominant power systems - Yong-Kyu Kim; Sang-Ho Lee; Gyu-Sub Lee (iEnergy)
In this paper, a strength-constrained unit commitment (UC) model incorporating system strength constraints based on the weighted short-circuit ratio (WSCR) is proposed. This model facilitates the comprehensive assessment of area-wide system strength in power systems with high inverter-based resource (IBR) penetration, thereby contributing to the mitigation of weak grid issues. Unlike traditional models, this approach considers the interactions among multiple IBRs. The UC problem is initially formulated as a mixed-integer nonlinear programming (MINLP) model, reflecting WSCR and bus impedance matrix modification constraints. To enhance computational tractability, the model is transformed into a mixed-integer linear programming (MILP) form. The effectiveness of the proposed approach is validated through simulations on the IEEE 5-bus, IEEE 39-bus, and a modified Korean power system, demonstrating the ability of the proposed UC model enhancing system strength compared to the conventional methodologies.